Strategi komunikasi KPID Jawa Timur dalam penyelenggaraan pengawasan siaran pemilihan kepala daerah (Pilkada) tahun 2020 - Ellyda Retpitasari; Muhammad Faqih (Islamic Communication Journal, 2021)
The purpose of this study is to analyze the communication strategy in the implementation of the 2020 Pilkada broadcast supervision with an analytical knife of pervasive presence theory. The method used in this research is a qualitative research method with a descriptive approach. The results of the research on the communication strategy of the East Java KPID in the Implementation of the 2020 Regional Election Broadcasting Supervision include; The East Java KPID strategy chose the communication target of broadcasting institutions consisting of Local Public Broadcasting Institutions (LPPL), Private Broadcasting Institutions (LPS), Community Broadcasting Institutions (LPK), and Subscribed Broadcasting Institutions (LPB) regarding news, broadcasting and advertising campaigns for the general election simultaneous regional heads in 2020; Meanwhile, for communication and message delivery methods, KPID conducts socialization and technical guidance by forming a team of volunteers to monitor regional election broadcasts in 19 regencies/cities throughout East Java. As for the communication strategy that must involve stakeholders, the East Java KPID synergizes with stakeholders including academics, East Java BAWASLU, 19 East Java Regency/City BAWASLU, East Java JPPR, and East Java KIPP.